Catheter ablation in patients on mechanical circulatory supports for cardiogenic shock - Milan Dusik; Stepan Havranek; Daniel Rob; Jan Šimek; Martin Valek; Zdenka Fingrova; Tomas Boucek; Jan Pudil; Ales Linhart; Jan Belohlavek (PLoS ONE, 2025)
Short-term mechanical circulatory supports (MCS) are used to stabilize patients with severe cardiogenic shock (CS). Catheter ablation may be an option to suppress recurrent arrhythmias preventing MCS weaning. We retrospectively analysed a dedicated registry to identify CS patients who underwent a catheter ablation between January 2020 and August 2024 for treatment resistant and hemodynamically significant arrhythmias while being on the MCS. Patients with supraventricular and ventricular tachycardias (SVT/VT) were analysed separately. Nine patients (8 males, 69 [IQR 60;74] years) were ablated for a refractory VT. Impella CP was used in 6 patients, VA ECMO in 2 patients, and 1 patient was on ECPELLA. Seven patients (78%) were successfully weaned off the MCS after the catheter ablation. 3 patients (33%) died within 30 days. The arrhythmia recurred in 5 patients (56%). Significant complications of MCS were reported in 6 patients (66%). The catheter ablation was complicated in one patient. SVT ablation was performed in 4 patients (3 males, 73 [IQR 67; 78] years, 1x VA ECMO, 2x Impella CP, 1x Impella 5.5). Three patients with atrial fibrillation were treated by a non-selective AV node ablation (pace and ablate strategy). One patient underwent an ablation of focal atrial tachycardia. The MCS was successfully explanted in all patients and no patient died in 30 days. The MCS use was complicated in one patient. Catheter ablation of refractory arrhythmias in CS patients treated by MCS is a safe and feasible approach to facilitate the MCS weaning process.